An Indoor Laboratory Simulation and Evaluation on the Aging Resistance of Polyether Polyurethane Concrete for Bridge Deck Pavement - Xu, Shifa; Xu, Meng; Zhang, Yexing; Guo, Yutao; Peng, Geng; Xu, Ying (Frontiers in Materials, 2020)
Polyether Polyurethane Concrete (PPC) is a new engineering material used for bridge deck pavement. In this paper, the aging resistance performance of PPC for long-term service is evaluated. Based on the actual climate and environment conditions of bridge deck pavement, the indoor laboratory simulation considering various environmental factors was first proposed, and then the indoor accelerated aging tests of PPC were carried out. Finally, the Cantabro test, the low temperature bending beam test, the rutting test, the splitting test under freeze-thaw cycle and four point bending fatigue test were conducted on the aged PPC specimens. The performances of anti-loose, resistance to permanent deformation, low temperature, water stability and fatigue resistance were evaluated and compared with SBS modified asphalt mixture (SBSM). Test results showed that PPC had good anti-aging performance, and the road performance of PPC after aging was still better than that of non-aging SBSM, which can be used for the long-term service as a bridge deck pavement material.